Suspension kinematic structure for passive control of vehicle attitude. (4th August 2014) - Raghavan, M.
The motion geometry of an independent suspension linkage have significant influence on vehicle behaviour. We state the geometric requirements for optimal vehicle performance as two sets of specifications, one on wheel–road kinematics and the other on sprung mass–road kinematics. As most current passenger cars are equipped with passive single–degree–of–freedom independent suspensions, we evaluate such linkages in terms of their potential to meet these requirements. We show that: (1) for cars which roll, camber and track width control are not achievable; (2) many current suspensions display undesirable for ride feature known as bump steer; (3) cars which maintain constant track width during straight–line motion cannot achieve zero roll during turns; (4) zero pitch during straight–line acceleration is not achievable if the accelerating inputs are provided at only one end of the vehicle. We propose novel multi–degrees–of–freedom suspensions which are capable of passive control of vehicle roll and ditch, our solutions rely on the inclusion of joints in the suspension linkage in such a way that they are always reciprocal to the external forces exerted by the environment on the automobile. As a rule, these external forces produce no undesirable motions of the suspension linkage and our designs are therefore passive. The design methodology used herein may also be extended to camber control arrangements in which the jounce–rebound motions of the wheel are decoupled from the camber degree–of–freedom. However, the camber, roll, and pitch control capabilities are achieved at the cost of increased mechanical complexity in the suspension linkage.